2007
DOI: 10.1111/j.1468-3156.2007.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

No One Knows: offenders with learning difficulties and learning disabilities

Abstract: Accessible summary Nobody knows how many people with learning difficulties get into trouble with the police. This article is about a project called No One Knows. It is finding out what happens when people with learning difficulties get into trouble with the police. Sometimes when people with learning difficulties get into trouble with the police they have to go to court. Sometimes they are sent to prison or have to visit a probation officer. Young people with a learning difficulty might have to go to a youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 6 publications
5
51
0
Order By: Relevance
“…With reference to the British project 'No One Knows' (Talbot & Riley 2007), there are several ways to approach those people with ID who offend or are alleged to have committed offences. 'No One Knows' is run by the Prison Reform Trust and has aimed to initiate changes for people with learning difficulties and learning disabilities who are referred to the criminal justice system.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to the British project 'No One Knows' (Talbot & Riley 2007), there are several ways to approach those people with ID who offend or are alleged to have committed offences. 'No One Knows' is run by the Prison Reform Trust and has aimed to initiate changes for people with learning difficulties and learning disabilities who are referred to the criminal justice system.…”
Section: Discussionmentioning
confidence: 99%
“…As of 2007 there was still no routine screening made to determine the ‘nature and extent’ of learning disabilities in the offender population (Talbot & Riley 2007). However one prevalence study based on research at HMP Liverpool indicated that approximately 30% of prisoners have an IQ of less than 80 (Hayes et al.…”
Section: Police Suspects and Defendantsmentioning
confidence: 99%
“…In other words, the over-representation of persons with learning disabilities in the criminal justice system may have as much or more to do with disparate access to justice (social and legal) as it does to underlying rates of crime. In the criminal justice system, the voices of persons with learning disabilities are rarely heard (Loucks 2007;Talbot & Riley 2007). Unfortunately, the same appears to be true of research about the criminal justice system.…”
Section: Introductionmentioning
confidence: 99%